KINERJA PEMASOK DALAM RANTAI PASOKAN MAKANAN KEMASAN : SUATU KAJIAN KASUS DI INDONESIA - Martadisastra, Dedie S. (Manajemen Bisnis Kompetensi, 2017)
ABSTRACT The purpose of this study is to understand the development of supplier performance in domestic packaged processed food supply chain which is influenced by competition condition and buyer power of retailers. The paper presents the results of a survey of suppliers of the package processed food of micro up to large scale enterprises and it is part of a broader study of supplier performance in the package processed food supply chain. The findings of the research result indicate the heterogeneity of the performance of the package processed food suppliers in modern retail supply chains. How suppliers are faced with competition, buyer power, supply chain strategy and market share, but on the other hand suppliers tend to be influenced by the way suppliers deal with modern retailers. it may be indicated that some suppliers benefit from the presence of modern retailers, but they face some of the challenges posed by buyer power that cause some terms of relationships to be unfair, unilateral price fixing, and poor supervision so that the development and growth of supplier performance are subject to limitations. The study attempts to demonstrate empirical research results in Indonesia to measure supplier performance in the modern retail package processed food supply chain influenced by competition and buyer power. The further research is needed to refine the results of this initial study.Keywords – Supplier performance, The packaged processed food supply chain, Competition, Buyer power.